Clinical Practice Guideline for the treatment of COVID-19 in the Social Security of Peru (EsSalud) - Pecho-Silva, Samuel (2022)
Introduction: Since the beginning of the COVID-19 pandemic, different drugs and medications have been used for the prevention and treatment of COVID-19 infection. Likewise, various investigations have been carried out to evaluate the efficacy and safety of these interventions, many of which have been shown to generate more harm than benefit for the patient, for this reason it is necessary to standardize the management of adult patients with COVID-19 in our context. Objective: To provide evidence-based clinical recommendations for the management of adults with COVID-19. Methods: A guideline development group (GEG) was formed that included medical specialists and methodologists. For its elaboration, GEG decided to carry out a rapid adaptation of the Guide for the care of critical adult patients with COVID-19 in the Americas of the Pan American Health Organization (PAHO) as well as to carry out searches for novo questions. For the formulation of the recommendations, the evidence frameworks for the decision (EtD) of the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology were developed. Results: This CPG addressed 28 clinical questions, divided into three topics: prevention, diagnosis and management. Based on these questions, 33 recommendations (16 strong and 17 conditional), 26 good clinical practices (GCP) and 2 flowcharts were formulated. This CPG was published in its third version in December 2021. Conclusion: This article summarizes the methodology and evidence-based conclusions of the CPG for the management of adults with COVID 19 in EsSalud.